Promoting Food Tourism through Leading Local Products in Padang, Indonesia - Wati, Linda; Safnedi, Sefnedi; Yuliviona, Reni; Rosha, Zhesasina; Azliyanti, Elfitra; Dores, Dedi; Almauli, Rizki; Flora, Anisa Septa Dwi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Food tourism, or culinary tourism, has become an important driver in maintaining regional identity, affirming community values, and contributing significantly to regional development. Potato dodol is a traditional food product that has been an important part of the local culinary wealth in various regions of Indonesia. This research aims to identify and overcome the problems faced by the local potato dod dol industry, as well as develop innovative strategies to make potato dool a typical souvenir that is sought after by tourists. With a focus on authentic experiences, innovation in culinary events, and the use of social media, culinary tourism can continue to grow and provide sustainable benefits for local communities. Through a holistic and sustainable approach, food tourism not only provides an immersive experience for tourists but also brings sustainable benefits to the community.